Morphodynamics of the Cávado estuary inlet (NW Portugal) - Loureiro, Eduardo (2005)
The Cávado estuary inlet is situated in the coastal zone of Esposende (NW Portugal) where sandy beaches have migrated inland and thinned, and cliffs have retreated rapidly over the last years. The coastal zone of Esposende extends over 15 km from the Neiva River until Apúlia. The coastal segment of Esposende can be considered of mixed energy and wave-dominated type, according to DAVIS and HAYES (1984). The local tide is mesotidal and semidiurnal, with a maximum equinoctial spring tide high-water level of 3.9 m, a minimum low-water level of 0.2 m, and a mean spring tide of 3.49m (data from Instituto Hidrográfico da Marinha). The inlet is a natural feature of the Cávado estuary, subject to silting up, and enclosed between a breakwater on the northern side and the end of a migrant sandy spit on the southern side. Recently, it was suggested that the best option for decreasing silting-up and increasing navigability, would be to build two breakwaters and artificially manage the inlet. This proposal was not accepted by all concerned and is presently frozen. Behind the spit lies the town of Esposende, and so it is crucial as its natural defence against sea incursions. Several times the sea overwashed the spit, and broke through twice during the last twenty years. The present study concerns the period between 1991 and 2003. Using the hydrographical maps of 1991, 1992 and 2001, and topo-hydrographic surveys of 2002 and 2003, the sedimentary budget of the inlet, and the morphological changes of the flood and ebb tidal deltas were calculated. Moreover, two hydrodynamic mathematical models and a sediment transport mathematical model were implemented, in order to assess the bottom morphodynamic behaviour at the inlet. The first one is a two-dimensional hydrodynamic (2DH) model that was created using the RMA2 software (WES-HL, 1996). The river stretch considered in this finite elements model begins downstream of the Angelino weir and ends in the Atlantic Ocean.